Preventive and therapeutic effects of ginger on bowel disease: A review of clinical trials - Lemlem Gebremariam Aregawi; Teferi Gebru Gebremeskel; Csiki Zoltan (Elsevier, 2024)
Introduction: Ginger has been integrated into various cultural traditions, including traditional Chinese medicine (TCM), where it is highly valued for its preventive and therapeutic efficacy. In traditional Chinese medicine (TCM), ginger is renowned for its ability to support digestive function by stimulating digestive juices, promoting gastric motility, and relieving gastrointestinal discomfort. This systematic review aimed to summarize ginger's preventive and therapeutic effects on bowel disorders and to update the current developments. Methods: Clinical trials published in English were searched in PubMed, Scopus, EMBASE, Web of Science and Clinical Trials databases with keywords from inception to August 2023. The search protocol was performed under the Preferred Reporting Items for Systematic Reviews and Meta-analysis (PRISMA) guidelines and registered in PROSPERO with registration number CRD42022378544. Due to the small sample size and the heterogeneity of studies, a narrative synthesis without meta-analysis is reported. Results: In the current review, evidence of ginger's effect on bowel disorders is reported. A daily dose of 2000 mg of ginger is beneficial for reducing inflammation, dyspepsia, colorectal cancer and ulceration in the digestive tract of patients with IBS and IBD. Because of the heterogeneity and limited number of studies, the results may not be as powerful as finding significant results. Discussion: Despite the small number of studies and the large heterogeneity, the majority of the studies have shown the Chinese traditional medicine, ginger's effect on bowel disorders. However, due to the limited number of studies and some inconsistencies, more controlled clinical trials with different dosages and duration are needed to obtain a firm conclusion.